Teacher's Illocutionary Acts in Online Learning Interactions - Effendi, Anwar; Sukinah, Sukinah (Universitas Pendidikan Ganesha, 2021)
Speech acts happen within the communication between teachers and students in online learning interactions. This study aims to describe the forms of illocutionary acts and representations of an Indonesian teacher's power strategies in online learning interactions through WhatsApp and Google Classroom. A descriptive qualitative was used to garner written conversations between the teacher and the students. This study involves an Indonesian language teacher and students, totaling 36 students. The data was gathered from written conversational speeches conveyed by the teacher and students through WhatsApp and Google Classroom during online learning. The data was analyzed using Miles and Huberman's model, including data collection, data reduction (data presentation), drawing temporary conclusion and verification, and conclusion and recommendation. The study reveals several types of illocutionary acts, such as assertive, directive, expressive and commissive – while no types of illocutionary acts are found. The teacher's representation of the power strategy in online learning interactions includes speech control, threatening, and being angry with insinuation.